Transformative Leaders: Reflection on Priesthood in the Midst of Covid-19 Pandemic in the District of Sleman - Yogyakarta - Stanislaus Eko Riyadi (P3TK, Sanata Dharma University, 2020)
Every darkness brings its own hidden light. The Covid-19 pandemic has shocked everyone and forced them to think about their existence and identity in a new fashion. This pandemic creates a crisis and a challenge to pass through this tough experience to a richer mode of life. Priests are called to think again about their identity and the meaning of being a priest in this pandemic. This research aims to know creative ways of the priests in the District of Sleman to undergo their mission as leaders of the Catholic community, especially in leading the parish to be a transformative Church that commits herself to solidarity and responsibility to the suffering of the people without any discrimination. Observation has been taken through a quantitative research and deep discussion with personal experiences of the priests. In this pandemic, any priest is called to take the first step to engage themselves in a web of cooperation and collaboration with people from different backgrounds. Priests are called to transform themselves to be able to lead other people into transformation. They should be transformative leaders of the community.